Supportive care needs in Hong Kong Chinese women confronting advanced breast cancer. Issue 5 (19th June 2012) - Au, Angel; Lam, Wendy; Tsang, Janice; Yau, Tsz‐kok; Soong, Inda; Yeo, Winnie; Suen, Joyce; Ho, Wing M.; Wong, Ka‐yan; Kwong, Ava; Suen, Dacita; Sze, Wing‐Kin; et al.
Abstract Background Women with advanced breast cancer (ABC) are living longer, so understanding their needs becomes important. This cross‐sectional study investigated the type and extent of unmet supportive care needs in Hong Kong Chinese women with advanced breast cancer. Methods Face‐to‐face interviews were conducted among women with stage III or stage IV disease mostly awaiting chemotherapy (76%) to identify unmet needs using the Supportive Care Needs Survey Short Form, psychological morbidity using the Hospital Anxiety and Depression Scale, symptom distress using the Memorial Symptom Assessment Scale, and satisfaction with care using the Patient satisfaction questionnaire (PSQ‐9). Results About 27–72% of 198/220 (90%) women (mean age = 53.4 ± 9.74 (standard deviation) years) identified needs from the health system, information, and patient support (HSIPS) domain as the top 15 most prevalent unmet needs. 'having one member of hospital staff with whom you can talk to about all aspect of your condition, treatment, and follow‐up' was most cited by 72% of the patients, with remaining unmet needs addressing mostly desire for information. Unmet need strength did not differ between women with stage III and stage IV disease, whereas women with first time diagnosis reported greater health system and information unmet needs compared with women with recurrent disease. Stepwise multiple regression analyses revealed that symptom distress was consistently positively associated with all but sexuality need domains, whereas low satisfaction with care was associated with HSIPS (β = 3.270, p < 0.001) and physical and daily living (β = 2.810, p < 0.01) domains. Discussions Chinese women with ABC expressed need for continuity of care and improved information provision. High symptom distress was associated with lower levels of satisfaction with care. These unmet needs appear to reflect current care services shortcomings. Copyright © 2012 John Wiley & Sons, Ltd.